SELF-AFFIRMATION AS A SOCIAL MEDIA CULTURAL CONSTRUCTION: A STUDY OF ERICK THOHIR'S POLITICAL EXPRESSION ON TIKTOK - Andika Hendra Mustaqim; Nanang Haroni (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
Abstract: Self-affirmation is an affirmation that reflects a person's views and ways of thinking through statements and attitudes. It is often associated with someone's position that shows the vision and mission that is carried out. Self-affirmation can be shown by people through various content on social media, including TikTok. For government officials or politicians, self-affirmation is an attempt to form an image on social media by displaying various political expressions. This study aims to explore the strategy and impact of self-affirmation as an image construction on Erick Thohir's TikTok account. By using qualitative content analysis, this study seeks to reveal self-affirmation with thematic analysis, which related to Nahdatul Ulama (NU) and the Indonesian Football Association (PSSI). This research found that the self-affirmation strategy used by Erick Thohir on TikTok is to prioritize creative and entertaining content. The impact of the self-affirmation that Erick Thohir pointed out was constructing his own identity with NU supporters and Indonesian football fans, as well as the formation of political polarization. Various contents on TikTok are able to support Erick Thohir's self-affirmation in his efforts to become a candidate for vice president in the upcoming 2024 elections. Keywords: Self Affirmation; Social Media Image; Expression; TikTok; Erick Thohir Abstrak: Afirmasi diri merupakan afirmasi yang mencerminkan pandangan dan cara berpikir seseorang melalui pernyataan dan sikap. Seringkali dikaitkan dengan jabatan seseorang yang menunjukkan visi dan misi yang diembannya. Penegasan diri bisa ditunjukkan masyarakat melalui berbagai konten di media sosial, termasuk TikTok. Bagi pejabat pemerintah atau politisi, afirmasi diri merupakan upaya membentuk citra di media sosial dengan menampilkan berbagai ekspresi politik. Penelitian ini bertujuan untuk mengeksplorasi strategi dan dampak afirmasi diri sebagai konstruksi citra pada akun TikTok Erick Thohir. Dengan menggunakan analisis isi kualitatif, penelitian ini berupaya mengungkap afirmasi diri dengan analisis tematik, yaitu terkait Nahdatul Ulama (NU) dan Persatuan Sepak Bola Seluruh Indonesia (PSSI). Penelitian ini menemukan bahwa strategi afirmasi diri yang digunakan Erick Thohir di TikTok adalah dengan mengutamakan konten yang kreatif dan menghibur. Dampak dari penegasan diri yang diutarakan Erick Thohir adalah terkonstruksinya identitas diri di kalangan pendukung NU dan suporter sepak bola Indonesia, serta terbentuknya polarisasi politik. Beragam konten di TikTok mampu mendukung penegasan diri Erick Thohir dalam upayanya menjadi calon wakil presiden pada pemilu 2024 mendatang. Kata Kunci: Afirmasi Diri; Gambar Media Sosial; Ekspresi; TikTok; Erick Thohir